1985
DOI: 10.1029/ja090ia02p01619
|View full text |Cite
|
Sign up to set email alerts
|

Escape of suprathermal O+ ions in the polar cap

Abstract: Instruments on board the Dynamics Explorer (DE) 1 and 2 spacecraft have been used to investigate the characteristics of a very low‐energy (less than 10 eV) outflow of O+ ions at high altitudes over the polar cap. The measured O+ outflow has a relatively high Mach number (2–6) and a large flux (∼2×108 cm−2 s−1). A statistical study using 50 orbits of retarding ion mass spectrometer (RIMS) data indicates that the outflows occur during active magnetic conditions, lasting for several hours over large areas of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(43 citation statements)
references
References 48 publications
3
40
0
Order By: Relevance
“…As it increased with height it is interesting to speculate that this ion up¯ow may be associated with an out¯ow at the topside ionosphere and higher altitudes (Lookwood, 1982; Shelly et al, 1982;Yau et al, 1985;Waite et al, 1985). If this is indeed the case, the observation would be in agreement with Waite et al (1985) stating that the out¯ow of O + in the polar cap exhibits a wide spatial and temporal extent under active magnetic conditions, and that it is strongest in the 1000±1600 MLT sector. Satellite data are needed for a ®nal proof to identify any ion out¯ow above 1000 km during the corresponding period.…”
Section: Upward Ion¯owsupporting
confidence: 77%
“…As it increased with height it is interesting to speculate that this ion up¯ow may be associated with an out¯ow at the topside ionosphere and higher altitudes (Lookwood, 1982; Shelly et al, 1982;Yau et al, 1985;Waite et al, 1985). If this is indeed the case, the observation would be in agreement with Waite et al (1985) stating that the out¯ow of O + in the polar cap exhibits a wide spatial and temporal extent under active magnetic conditions, and that it is strongest in the 1000±1600 MLT sector. Satellite data are needed for a ®nal proof to identify any ion out¯ow above 1000 km during the corresponding period.…”
Section: Upward Ion¯owsupporting
confidence: 77%
“…The low energization also means that it is very difficult for O + ions to escape Earth's gravitational potential via this mechanism, and so very little O + is expected in the polar wind. Nevertheless, O + ions have been observed above the polar caps and in the lobes (Nagai et al, 1984;Waite Jr. et al, 1985;Abe et al, 1993;Su et al, 1998a). Many additional mechanisms have been proposed to explain this (see, e.g., Tam et al, 2007, for an overview).…”
Section: Introductionmentioning
confidence: 99%
“…Satellite observations of ion outflow at high altitudes (>5000 km) have been extensively studied in many previous works (e.g., Shelley et al, 1976;Lockwood et al, 1985;Waite et al, 1985;Yau et al, 1985;Chappell et al, 1987). Lockwood et al (1985) showed that occurrence of the heavy ion outflow depends on K p index by using the retarding ion mass spectrometer (RIMS) data obtained from the DE-1 satellite for 2 years.…”
Section: Relationship Between the Localized Electric Fieldmentioning
confidence: 99%